2020
DOI: 10.1038/s41598-020-64692-z
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the pond: genetic assignment detects lobster hybridisation

Abstract: American lobsters (Homarus americanus) imported live into Europe as a seafood commodity have occasionally been released or escaped into the wild, within the range of an allopatric congener, the European lobster (H. gammarus). In addition to disease and competition, introduced lobsters threaten native populations through hybridisation, but morphological discriminants used for species identification are unable to discern hybrids, so molecular methods are required. We tested an array of 79 single nucleotide polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 30 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…10,54 Hybridization research and management of its consequences has necessitated the search for various tools used in distinguishing hybrids from pure species and the increasing availability of molecular markers provides a powerful tool for evaluating the extent of crossbreeding and introgression in wild populations affected by introduction. 10,55 Based on analysis of mitochondrial DNA haplotypes, mitochondrial cytochrome oxidase I (COI) and nuclear microsatellite data, the hypothesis of an hybrid origining from invasive species population can be substantiated. 52 Kim et al 56 also reported accurate identification of hybrid between snow crabs using a genotyping assay based on a single nucleotide polymorphism (SNP) in the ITS-1 (internal transcribed spacer) region and the COI gene.…”
Section: Molecular Methods In Identification Of Natural Hybridization...mentioning
confidence: 99%
See 2 more Smart Citations
“…10,54 Hybridization research and management of its consequences has necessitated the search for various tools used in distinguishing hybrids from pure species and the increasing availability of molecular markers provides a powerful tool for evaluating the extent of crossbreeding and introgression in wild populations affected by introduction. 10,55 Based on analysis of mitochondrial DNA haplotypes, mitochondrial cytochrome oxidase I (COI) and nuclear microsatellite data, the hypothesis of an hybrid origining from invasive species population can be substantiated. 52 Kim et al 56 also reported accurate identification of hybrid between snow crabs using a genotyping assay based on a single nucleotide polymorphism (SNP) in the ITS-1 (internal transcribed spacer) region and the COI gene.…”
Section: Molecular Methods In Identification Of Natural Hybridization...mentioning
confidence: 99%
“…52,55,[91][92][93][94][95][96][97][98][99] Invasive hybridization is frequently associated with profoundly negative consequences, such as loss of genetic variation and adaptation. 10,55,92,100 Interspecific hybridization between introduced and native species has thus raised concerns about the genetic integrity and evolutionary viability of native taxa, particularly those under threat from other stressors. 52,92 Genetic introgression from hybridization with non-native species is a major consequence of human-facilitated species introductions, endangering endemic species through decreased fitness and local replacement.…”
Section: Hybridization With Invasive Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports of non-native American lobsters exhibiting symptoms like those of ESD housed in a public aquarium in Europe (van der Meeren, 2008) showing the apparent presence of this condition in European waters (these animals were caught locally). The susceptibility of hybrids of H. americanus x gammarus (Ellis et al, 2020) to ESD is also undetermined.…”
Section: Type 1 Shell Disease Displays Variable Severity Prevalence A...mentioning
confidence: 99%
“…In marine organisms, genome-wide SNP discovery has been of considerable assistance in improving our understanding of the degree of population genetic differences [ 12 , 13 ], detection of secondary contact [ 14 ], and the effect of local environmental adaptation [ 15 ]. The joint allele frequency spectrum (AFS) from genome-wide SNP data has recently been used successfully to investigate historical demography of several non-model marine species (e.g., [ 16 ]).…”
Section: Introductionmentioning
confidence: 99%